2014
DOI: 10.1002/mrc.4128
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in composition of extracts of natural products as monitored by in situ NMR

Abstract: The direct in situ NMR observation and quantification, based on the aldehyde -CH chemical shift region, of the inter-conversion of secoiridoid derivatives due to temperature and solvent effects is demonstrated in complex extracts of natural products without prior isolation of the individual components. The equilibrium between the aldehyde hydrate form and the dialdehyde form of the oleuropein aglycon of an olive leaf aqueous extract in D(2)O was shown to be temperature dependent. The resulting thermodynamic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Ellagic acid, 24-methylcholestanol ferulate, daidzein, and carnosic acid have been also described to possess anticancer activity. Oleuropein was reported as an anticancer, cardioprotective, gastroprotective, and hepato-protective compound . Two oleuropein aglycones, i.e., 3,4-DHPEA-EA and 3,4-DHPEA-EDA (the mono- and dialdehyde forms, respectively), were found among discriminating compounds. In addition to the role of cultivar-discriminating compounds, UHPLC/Q-TOF-MS analysis (whole phenolic profile) shows that artichoke leaf extracts provide an excellent source of health-promoting compounds, regardless the cultivar considered.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ellagic acid, 24-methylcholestanol ferulate, daidzein, and carnosic acid have been also described to possess anticancer activity. Oleuropein was reported as an anticancer, cardioprotective, gastroprotective, and hepato-protective compound . Two oleuropein aglycones, i.e., 3,4-DHPEA-EA and 3,4-DHPEA-EDA (the mono- and dialdehyde forms, respectively), were found among discriminating compounds. In addition to the role of cultivar-discriminating compounds, UHPLC/Q-TOF-MS analysis (whole phenolic profile) shows that artichoke leaf extracts provide an excellent source of health-promoting compounds, regardless the cultivar considered.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From the earlier mentioned it may be concluded that the analytical results are in agreement with those obtained with the use of HPLC‐DAD, preparative LC and LC‐SPE‐NMR, however, the present method has the following distinct advantages: (i) it can be applied in the analysis of complex plant extracts without any previous separation or isolation of the individual compounds; (ii) is rapid requiring about 30 min for recording 1D 1 H‐NMR spectra with sensitivity comparable to that obtained for aromatic protons; (iii) is very specific as the quantification is based on structure information of the OH signals which can be used as molecular “sensors” (Edmonds, ); (iv) is more selective than UV or other detectors. It remains to be investigated whether it can be applied in monitoring dynamic changes in composition of extracts of natural products in the NMR tube (Charisiadis et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The aldehyde/hydrate equilibrium was shown to be temperature and solvent dependent. The thermodynamic values of the Van't Hoff plot showed a significant entropy term that nearly compensates the effect of enthalpy at room temperature: while bonding of two oxygen atoms to the same carbon is energetically more favorable than double bonding to a single oxygen, the entropy decreases because the number of product molecules is smaller than the number of reactant molecules [11], and this equilibrium is also pH-dependent. Regarding the compounds studied in this work, aldehyde-hydrate equilibrium was observed in pyridinecarboxaldehydes: neutral conditions favor the free aldehyde, showing a hydration constant significantly smaller than the unity, while in pyridinecaboxyacids the hydrate is the major species [12].…”
Section: Introductionmentioning
confidence: 99%